(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تُعدُّ دراسات جدوى المشروعات بنظام BOT وعمليات تقييمها الاقتصادي والاجتماعي من المواضيع الهامة والحيوية لكل من المستثمر (شركة المشروع)، والحكومة مانحة الامتياز، سواء في الدول النامية أم المتقدمة، حيث تزداد أهمية تلك الدراسات الاقتصادية في الدول النامية لما تعانيه من ندرةٍ نسبية في مواردها الاقتصادية وعدم استخدامها بالكفاءة المطلوبة. وقد هدف البحث إلى دراسة إمكانية ترشيد القرارات الاستثمارية وإمكانية التعرف على الوقائع الاقتصادية الخاصة بكل مشروع، وإلى التفريق بين كلٍ من الربحية التجارية والربحية القومية ومعرفة أوجه الاختلاف بينهما لضرورة التوفيق بين أهداف القطاع الخاص وأهداف الدولة المضيفة لهذا النظام، وذلك من خلال تقويم أحد المشروعات السياحية المتعاقد عليها في سوريا وفق نظام BOT. هذا بالإضافة إلى بيان قدرة تلك المشروعات إلى تحقيقها الربحية التجارية بأنها قادرة على حل بعض المشكلات الاقتصادية والاجتماعية 1- البطالة 2-عجز ميزان المدفوعات 3-توزيع الدخل 4 -تحقيق التنمية المطلوبة . The BOT projects feasibility studies, their economic and social assessment are considered topics that are relevant and vital to each investor (a project company), and donor Government of excellence, whether in developed or developing countries. The importance of those economic studies in developing countries becomes great due to their relatively scarce economic resources which are not used in efficient way. The research aimed to study the possibility to rationalize investment decisions and the possibility to identify the specific economic situationns of each project, and to differentiate between the economic Profitability and national Profitability, and knowing the difference between them to coordinate between the objectives of private sector and the objectives of the host country of the system. This is by evaluating one of the tourism projects that are contracted in Syria, according to BOT. The research also aims to show the ability of these projects in addition to achieving commercial profitability that they can solve some economic and social problems such as 1- unemployment 2- deficiency Balance Payment, 3- income distribution 4- achieving the necessary development.